2022
DOI: 10.1111/roie.12622
|View full text |Cite
|
Sign up to set email alerts
|

China–US economic and trade relations, trade news, and short‐term fluctuation of the RMB exchange rate

Abstract: The trade war between the US and China affects the fluctuation of RMB exchange rate. We collect news on China-US trade policies and talks from January 2017 to July 2020. Results show that China-US dialogue and tariff imposition have the greatest impact on the percentage of RMB appreciation and depreciation. Additionally, tariff relaxation and increasing enterprise restrictions can cause a sharp appreciation and depreciation. "Policies" events and trade news from the US influence RMB fluctuations the most signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Sohag et al [ 23 ] demonstrated that the RUB appreciated in response to the rising oil prices and trade, while depreciation was caused by economic uncertainty. Guo and Chen [ 24 ] found that tariff restrictions profoundly impacted the Renminbi (RMB) exchange rate fluctuations. Similalry, the positive and negative events significantly caused the appreciation and depreciation of the RMB, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sohag et al [ 23 ] demonstrated that the RUB appreciated in response to the rising oil prices and trade, while depreciation was caused by economic uncertainty. Guo and Chen [ 24 ] found that tariff restrictions profoundly impacted the Renminbi (RMB) exchange rate fluctuations. Similalry, the positive and negative events significantly caused the appreciation and depreciation of the RMB, respectively.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Following China's entry into the World Trade Organization (WTO), its exports have seen significant growth. According to China's General Administration of Customs, merchandise exports were $513.9 billion in 2001 and surged to $2.65 trillion in 2019, reflecting active participation in the multilateral trade system and export growth through cooperation [6] .…”
Section: Expanding Multilateral Trade Partnershipsmentioning
confidence: 99%
“…Regarding previous literature, various recent studies have investigated the link between political relations and some macroeconomic variables. Guo & Chen (2023) report that trade tariffs and negative events/news can significantly depreciate the RMB vis-à-vis the US dollar. In addition, political frictions similarly matter for the exchange rate.…”
Section: Introductionmentioning
confidence: 99%